2022
DOI: 10.1002/hed.27051
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck pedicled flap autonomization using a new high‐resolution indocyanine green fluorescence video‐angiography device

Abstract: In head and neck oncologic surgery a reconstructive phase is often required and pedicled flaps are still a viable option, though they may need a pedicle division performed at a later stage. Several techniques are commonly used for perfusion assessment of the flaps, with indocyanine green (ICG) fluorescence video‐angiography representing a promising tool. We used ICG video‐angiography to evaluate the perfusion of two of the most commonly adopted pedicled flaps in the head and neck field (the supraclavicular and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Other authors warn against risk factors such as irradiation, atherosclerosis, and smoking [76,92,105]. However, the advent of modern monitoring techniques, such as indocyanine green angiography and contrast-enhanced ultrasonography, helped confirm the acquired independence of the flaps from their initial blood source [4,107,108].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors warn against risk factors such as irradiation, atherosclerosis, and smoking [76,92,105]. However, the advent of modern monitoring techniques, such as indocyanine green angiography and contrast-enhanced ultrasonography, helped confirm the acquired independence of the flaps from their initial blood source [4,107,108].…”
Section: Discussionmentioning
confidence: 99%
“…A right PMMCF was harvested (the left one had already been used in 2016) and transposed to fill the gap of tissue in between the trachea and oesophagus, with its skin paddle positioned to resurface the oesophageal side of the fistula (figure 4). Since the skin paddle harvested with the flap was quite small (as needed to close the fistula), we used indocyanine green (ICG) fluorescence video-angiography (ICG-VA) intraoperatively to assess its perfusion: we used a cut-off value of 25% for flap-to-normal skin ICG ratio (percentage) as a threshold of ischaemia (online supplemental video 1), as highlighted by our own experience and previous evidences 8 9. Ten days after surgery, a videofluoroscopic swallow study confirmed that the fistula had been successfully repaired, and the patient was able to resume oral feeding (figures 5 and 6).…”
Section: Case Presentationmentioning
confidence: 98%